Cólera en gestantes en el Hospital Nacional Cayetano Heredia, Lima-Perú. - SAONA, Pedro (2013)
All cases of cholera in pregnant women (84) admitted to Hospital Nacional Cayetano Heredia, Lima-Perú were reviewed from febraury 1st to May 31st, 1991. Most of the patients (90%) came from shanty towns sorrounding the hospital, their main complain was profuse watery diarrhea and vomiting. Vibrio cholerae 01 biotype El Tor serotype Inaba was identified as the causative agent. The 84 pregnant women represent less than 1% of all cholera patients attended at the hospital. Twenty patients requiered hospitalization because of sever dehydration; one developed acute renal failure. The proportion of pregnantwomen who requiered hospitalization was higher in those less than 20 years old (50%). Fetal loss ocurred mainly in young pregnant women (30%) and in 1nd trimester patients (7%). The treatment was based in oral or intravenous fluid replacement and early administration of antimicrobial agents.